2021
DOI: 10.3390/cryst11091136
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Pack Carburized SCM 420 Steel Processed Using Natural Shell Powders and Extended Carburization Time

Abstract: The feasibility of using coconut shell powder (CSP) and dog conch shell powder (DCSP) as carburizing media in the pack carburization of SCM 420 steel was investigated. The carbon content and surface hardness of the carburized specimens prepared with different CSP:DCSP ratios and carburizing durations were examined and compared. A CSP:DCSP ratio of 60%:40% and an extended carburizing time of 12 h were found to increase the carbon content of the carburized specimens to 1.14 ± 0.007 wt%. Furthermore, the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…12 (c). This is due to the fact that hardness increases with carbon content at an elevated temperature and time [ 19 ]. Intercritical heat treatment, also known as high-temperature heat treatment, is a quick and easy approach to creating ferrite/martensite dual-phase microstructure, which balances steel's ductility and strength.…”
Section: Resultsmentioning
confidence: 99%
“…12 (c). This is due to the fact that hardness increases with carbon content at an elevated temperature and time [ 19 ]. Intercritical heat treatment, also known as high-temperature heat treatment, is a quick and easy approach to creating ferrite/martensite dual-phase microstructure, which balances steel's ductility and strength.…”
Section: Resultsmentioning
confidence: 99%
“…Gambar 6 menunjukan terjadi penurunan nilai kekerasan pada penambahan 50% katalis [29], penambahan katalis menurut Suherman dalam bukunya menyebutkan bahwa penambahan katalis maksimal 40% [7], hal itu bersamaan dengan semakin banyaknya penambahan penggunaan katalis dan mempunya sifat mudah untuk terurai dari katalis jenis kalsium karbonat, maka jumlah gas CO2 yang dihasilkan dari reaksi dekomposisi akan terjadi peningkatan [30], di sisi lain, peningkatan penambhan penggunaan katalis yang tidak sebanding dengan sumber karboon akan mengurangi kapasitas karbon dalam media carburizing yang tersedia untuk bereaksi [30]. Dengan begitu, peningkatan jumlah gas CO2 yang dihasilkan dari reaksi dekomposisi tidak sebanding dengan ketersediaan karbon (C) dalam media carburizing untuk difusikan ke dalam permukaan baja, hal itu menyebabkan gas CO2 hanya berinteraksi tanpa terjadi penangkapan atom-atom karbon untuk melarutkannya ke dalam permukaan baja, yang akhirnya mengakibatkan penggunaan katalis kalsium karbonat dalam jumlah persentase yang berlebihan menyebabkan penurunan nilai kekerasan [31].…”
Section: Pengaruh Caco3 Terhadap Kekerasanunclassified
“…The present team has investigated that strombus turturella shell powder can be utilized as a catalyst in the carburizing of SCM420 steel in earlier investigations. The investigation's findings revealed that the pack carburizing procedure considerably improved the hardness and wear resistance of SCM 420 steel by employing coconut charcoal powder as a carbon source and Strombus Turturella shell powder as a catalyst [11][12][13]. However, the research examinations are still restricted to examining the impact of SCM 420 steel's wear properties on the variation in the catalyst percentages.…”
Section: Introductionmentioning
confidence: 99%